Formation of Indonesia's National Law System - Ramadhani Puji Astutik; Anita Trisiana (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2020)
The formation of Indonesia's national legal system cannot be separated from the politics of law, because it is used as a guide in the process of making and enforcing the law to achieve a dream and national goal. The formation of the legal system in Indonesia has not gone well, Indonesia should have its own law. By having its own law, Indonesia will have national identity and will be seen as advanced by other countries. The formation of the national legal system in Indonesia is heavily influenced by external elements. It should maintain all the material sources of law that already exist in Indonesia. The objective of this study is to describe the formation of the national legal system in the State of Indonesia. This study uses a normative approach by using secondary data from library materials. The results of this study indicate that the formation of a national legal system is a process of developing a legal system and along with its element. With the development of the national legal system, it must be able to replace the Dutch colonial legal products with its own legal products. The development of the national legal system is a way to make changes in Indonesian legal products that must be in accordance with the values that are in people's lives. In the process of legal development, it is impossible to be separated from a legal politics.